Integrating ScientificWorkflows with Scientific Gateways: A Bioinformatics Experiment in the Brazilian National High-Performance Computing Network - Mondelli, Maria Luiza; Galheigo, Marcelo Monteiro; Medeiros, Vívian; Bastos, Bruno F.; Gomes, Antônio Tadeu Azevedo; Mattoso, Marta; Vasconcelos, Ana Tereza R.; Gadelha Jr., Luiz M. R. (Anais do Brazilian e-Science Workshop (BreSci), 2016)
Bioinformatics experiments are rapidly and constantly evolving due improvements in sequencing technologies. These experiments usually demand high performance computation and produce huge quantities of data. They also require different programs to be executed in a certain order, allowing the experiments to be modeled as workflows. However, users do not always have the infrastructure needed to perform these experiments. Our contribution is the integration of scientific workflow management systems and grid-enabled scientific gateways, providing the user with a transparent way to run these workflows in geographically distributed computing resources. The availability of the workflow through the gateway allows for a better usability of these experiments.